2003
DOI: 10.1159/000072076
|View full text |Cite
|
Sign up to set email alerts
|

Tubo-Ovarian Abscess in Older Women: Is the Woman’s Age a Risk Factor for Failed Response to Conservative Treatment?

Abstract: Objective: To assess retrospectively if there is a trend of change in the epidemiology of tubo-ovarian abscess (TOA) and to define the epidemiologic, clinical and laboratory risk factors associated with failed response to conservative antibiotic therapy. Study Design: The charts of 60 patients, admitted with clinically and sonographically diagnosed TOA between January 1995 and December 2000, were reviewed. On admission, all patients were treated with broad-spectrum antibiotics, and were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 19 publications
4
26
2
4
Order By: Relevance
“…In our study, surgical treatment was necessary for 20 patients (26%). Success of medical treatment is associated with the following factors: age, abscess size, bilateral adnexal involvement, laboratory parameters (8).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, surgical treatment was necessary for 20 patients (26%). Success of medical treatment is associated with the following factors: age, abscess size, bilateral adnexal involvement, laboratory parameters (8).…”
Section: Discussionmentioning
confidence: 99%
“…PID is a polymicrobial infection characterized by inflammation of the upper genital tract, including endometritis, salpingitis and pelvic peritonitis [6][7][8][9]. Secondary TOA can rarely arise from inflammatory bowel disease, diverticulitis, appendicitis, pelvic surgery, pelvic malignancy, or ovarian hyperstimulation [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic therapy should cover Neisseria gonnorrhoe, Chlamydia trachomatis and anaerobes, Gram-negative facultative bacteria and Streptococcus species [2]. The predisposing factors in the development of a TOA include nulliparity, sexual activity, previous episodes of PID, multiple sexual partners, lower socioeconomic status and the use of intrauterine devices [6,9]. Particularly, IUDs are associated with an increased risk for ascending infections [9] with high absolute numbers, especially as they are considered worldwide as one of the most preferred methods of reversible contraception [10].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the mean age of all 60 patients was >40 years. The authors thus concluded a new trend in the epidemiology of TOA, indicating a more aggressive compared to younger women [6,7]. One suggestion is that previous asymptomatic or subclinical infections may progress silently to the TOA stage over a long period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation